Rancang Bangun Sistem Pengaman Sepeda Motor Menggunakan Sensor Sentuh - Surip Surip; Angga Septiyanto; Rizqi Fitri Naryanto; Hadromi Hadromi; Bunyamin Bunyamin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This research aims to design and develop a touch sensor-based motorcycle safety system that integrates microcontroller technology and fingerprint sensors. The background of the research is based on the high rate of motorcycle theft in Indonesia, as well as the weak conventional security system that is easy to break into. The research method used is Research and Development (R&D) which includes the design, design validation, product manufacturing, and performance test stages. The development process includes problem identification, literature study, design design (electronic and mechanical), design validation and revision, product manufacturing, product validation and revision, system performance test, and data analysis. The system is designed using Arduino Nano and R503 fingerprint sensors, with the aim of restricting vehicle access to only verified users. The results of the study show that the developed safety system is able to limit vehicle access only to users whose fingerprints have been verified. Based on the feasibility test by experts and users, the system obtained a score of 90% on the design and feasibility aspects, and 85% on the performance test. These results show that the system is feasible to use and functions optimally. It was concluded that this fingerprint sensor-based motorcycle safety system is effective as an additional safety alternative to prevent theft. Further development can be done by adding features such as alarms, GPS tracking, and mobile app integration.